The Challenges Imposed by Dengue, Zika, and Chikungunya to Brazil - Zanotto, Paolo Marinho de Andrade; Leite, Luciana Cezar de Cerqueira (Frontiers in Immunology, 2018)
Brazil has a well-established immunization program in which vaccines are provided through the Public Health System free of charge to the whole population, obtaining high coverage and reducing the incidence of important infectious diseases in children and adults. However, the environmental changes and high mobility rates of the population occurring in the last decades have triggered the sequential introduction of a series of vector-borne emerging infectious diseases, such as Dengue, Zika and Chikungunya, that have imposed a considerable burden on the population, with yet unmet solutions. The first to be introduced in Brazil was the Dengue virus, reaching epidemic levels in 2010, with over 1 million cases annually, maintaining high infection rates until 2016. Brazil has invested in vaccine development. The Zika virus infection, initially assumed to have appeared during the World Cup in 2014, was later shown to have arrived earlier in 2013. Its emergence mobilized the Brazilian scientific community to define priorities and strategies, that rapidly investigated mechanisms of pathogenesis, differential diagnostics and determined that Zika virus infection per se causes relatively mild symptoms, however, in pregnant women can cause microcephaly in the newborns. The diagnostics of Zika infection is confusing given its similar symptoms and cross-reactivity with Dengue, which also hindered the appraisal of the extent of the epidemics, which peaked in 2015 and finished in 2016. Another complicating factor was the overlap with Chikungunya virus infection, which arrived in Brazil in 2014, being prevalent in the same regions, with similar symptoms and cross-reactivity with both Dengue and Zika. Although Dengue infection can be fatal and Zika infection in pregnant woman can lead to newborns with microcephaly or an array of neurodegenerative manifestations, the Chikungunya infection is a debilitating disease leaving chronic sequelae, which unfortunately has received less attention. The precise differential diagnostics of Dengue, Zika and Chikungunya will be necessary to evaluate the actual extent of each of these diseases during this overlapping period. Here we review the impact of these emerging infections on public health and how the scientific community was mobilized to deal with them in Brazil.